Volume 6A: Materials and Fabrication 2013
DOI: 10.1115/pvp2013-97185
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Improvement of Welded Elements and Structures by Ultrasonic Peening

Abstract: The ultrasonic impact treatment (UIT) is relatively new and promising process for fatigue life improvement of welded elements and structures. In most industrial applications this process is known as ultrasonic peening (UP). The beneficial effect of UP is achieved mainly by relieving of tensile residual stresses and introducing of compressive residual stresses into surface layers of a material. The secondary factors in fatigue improvement by UP are decreasing of stress concentration in weld toe zones and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 9 publications
(4 reference statements)
0
24
0
3
Order By: Relevance
“…Other factors for the beneficial effect of UIT are decreasing of stress concentration in weld toe zones and enhancement of mechanical properties of the surface layer [4,8,13,14]. Fatigue testing of welded specimens showed that UP is the most efficient improvement treatment as compared with traditional techniques such as grinding, TIG-dressing, and hamming peening [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors for the beneficial effect of UIT are decreasing of stress concentration in weld toe zones and enhancement of mechanical properties of the surface layer [4,8,13,14]. Fatigue testing of welded specimens showed that UP is the most efficient improvement treatment as compared with traditional techniques such as grinding, TIG-dressing, and hamming peening [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For control and determination of hydrogen concentration we use the hydrogen analyzer AV-1. The precision hydrogen analyzer AV-1 has been designed for hydrogen detection in metals and alloys under the plant laboratory conditions during the outgoing control provided for different alloys [8][9][10][11][12]. The operating principle of the analyzer is mass-spectrometric.…”
Section: Control Of Hydrogen Concentrationmentioning
confidence: 99%
“…One of these methods is Ultrasonic Peening treatment. Ultrasonic Peening (UP) is a promising technology in the application of High Power Ultrasound treatment for fatigue life improvement of welded structures [12,13]. The treatment is executed with a pin, from 2 to 5mm in diameter made from high strength steel.…”
Section: Decreasing the Concentration Of Hydrogen During Operation Prmentioning
confidence: 99%
“…In a study aimed at evaluation of the effectiveness of UP application in welding application, three series of largescale welded samples, designed as shown in Figure 3a, were subjected to fatigue testing in as-welded condition, with UP applied before fatigue testing and with UP applied after fatigue loading with the number of cycles corresponding to 50% of the expected fatigue life of samples in as-welded condition [9].…”
Section: Manufacturing and Rehabilitationmentioning
confidence: 99%
“…In most industrial applications this process is also known as ultrasonic peening (UP) [8][9][10][11][12]. The beneficial effect of UIT/UP is achieved mainly by relieving of harmful tensile residual stresses and introducing of compressive residual stresses into surface layers of materials, decreasing of stress concentration in weld toe zones and enhancement of mechanical properties of surface layers of the material.…”
Section: Introductionmentioning
confidence: 99%